Metaphysics of the Dead and Existence in the Poetry of John Pepper Clark (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
Critical investigations into the works of John Pepper Clark, have always paid attention to the social thrusts of his works and his fidelity to the Nigerian landscape which he has copiously deployed in the heterogeneous corpus of his poetry. However, the social vents of his poetry have become the most controversial on account of an alleged token attention, inconsistency or disinterestedness with the social traumas that pervade his space. This article conducts a postcolonial study on one of the ardent subjects that pervade the poetry of John Pepper Clark. While identifying with the fact that responses to social traumas, through an engagement with the political issues of the society is just one of the purposes of poetry, this paper identifies with Clark’s philosophy of poetry which is mostly concerned with the subject of life and existence discernible, mostly, in his thoughts on death and dying.  After looking at the diverse tentacles of the subject, the paper concludes that Clark’s death consciousness has not only validated some Africanised values that his discussions about death and dying are his moralising agents through which he dispenses mitigating pills on the social ills that have pervaded his postcolonial space.
Keywords: J. P. Clark; motifs; heterogeneity; existence; metaphysics